Managing business continuity in the Arctic: Experiences from mining - Taarup-Esbensen, Jacob (Risk Analysis, 2023)
This article presents a model for business continuity capacity, which shows how organizations can analyze possible gaps in their business continuity capability and thereby increase their capacity to recover value-adding critical activities. Using an example of a flooded mine on Svalbard, the study investigated how the mining company Store Norske Spitsbergen Coal Company (SNSK), with considerable experience with similar events and an excellent safety record, could fail to manage a well-known event and reduce recovery times of its critical activities. The analysis explored how experience in safety and incident management does not necessarily mean that these abilities are transferable to a new but similar event. The study sought to answer the research question: To what extent does SNSK's systematic work with safety, and experience with flooding events, improve business continuity capacity? In the Arctic, emergency response can take hours or days to arrive after the event. A structured recovery system can support pre-existing platforms aimed at safety, to include the critical activities needed to ensure an organization's overall survival. Systematic work can improve performance and make the organization engage in a virtuous cycle by implementing management structures, risk identification systems, competency development, and processes for the in situ evaluation of hazards. However, as seen here, the organization needs to pay attention to changes that could affect risk assessments and threat levels well-known events. These insights can be utilized by other organizations seeking synergy when strengthening their safety and business continuity performance. publishedVersion